E-Bayesian analysis of the Gumbel type-ii distribution under type-ii censored scheme - Reyad, Hesham; Ahmed, Soha Othman (International Journal of Advanced Mathematical Sciences, 2015)
This paper seeks to focus on Bayesian and E-Bayesian estimation for the unknown shape parameter of the Gumbel type-II distribution based on type-II censored samples. These estimators are obtained under symmetric loss function [squared error loss (SELF))] and various asymmetric loss functions [LINEX loss function (LLF), Degroot loss function (DLF), Quadratic loss function (QLF) and minimum expected loss function (MELF)]. Comparisons between the E-Bayesian estimators with the associated Bayesian estimators are investigated through a simulation study.